Inhibition of Biofilm Formation in Bacteria by Essential Oils - Alshilawi, Mashaeal Saud; Foster, Howard (Journal of medical and pharmaceutical sciences, 2020)
The formation of S. epidermidis and P. aeruginosa biofilms were successfully inhibited in the presence of sub-inhibitory concentrations of S. aromaticum (clove) and L. angustifolia (lavender) essential oils. These substances achieved good in-vitro test results. On the other hand, pure and organic types of N. sativa (black seed) essential oil did not exhibit any inhibitory effects on the biofilm formed by the tested bacteria. Although the tested essential oils may share a similar mechanism of action, ANOVA analysis showed strong statistical differences between all essential oils at their sub-MIC levels, and also identified two different trends, biofilm inhibitors, represented by S. aromaticum (clove) and L. angustifolia (lavender) oils, and biofilm stimulators, represented by both types of N. sativa (black seed) oils. A more thorough perspective on the research question could be achieved by considering the various elements that have essentially contributed to the processes and the findings within this study.